Black soldier fly larvae replace traditional iced trash fish diet to enhance the delicious flavor of Chinese mitten crab (Eriocheir sinensis) - Qiu, Jian-Feng; Luo, Cheng; Ren, Li-Hua; Li, Wei; Dai, Tai-Ming; Wang, Guang; Sun, Xiao-Ning; Moua, Kou-Chang Chong; Sima, Yang-Hu; Xu, Shi-Qing (Frontiers in Marine Science, 2023)
Chinese mitten crabs (Eriocheir sinensis) are traditionally fed iced trash fish, but the industry is facing problems such as low breeding safety. Black soldier fly (Hermetia illucens) is an alternative protein source in animal diets, including diets for aquatic animals, due to its high nutritional value. However, studies on the effects of black soldier fly on the flavor characteristics of aquatic animals are still limited. In the present study, we investigated the effects of the complete replacement of iced trash fish with black soldier fly larvae during the fattening period of Chinese mitten crab on the flavor molecule contents and evaluation indices. The levels of free amino acids and nucleotides were determined in three edible parts (muscle, hepatopancreas, and gonads) of crab. Taste activity value analysis showed that glutamic acid, glycine, alanine, and arginine were the main amino acids contributing to the umami taste and sweetness, while histidine, lysine, valine, and methionine were the main amino acids contributing to the bitterness. Equivalent umami concentration (EUC) analysis showed that female gonads had the strongest umami taste, followed by the hepatopancreas and muscle. Sweetness value (SWT) analysis showed that the sweetness of muscle was the highest. Feeding black soldier fly larvae affected the flavor characteristics of crabs with tissue and sex differences. The EUC of the female gonads and SWT of the muscle were significantly increased. Meanwhile, the EUC of the hepatopancreas and SWT of the gonads were slightly decreased in male crabs. Our results indicate that the complete replacement of iced trash fish with black soldier fly larvae during the fattening period significantly enhances the flavor characteristics of crabs based on the contents of flavoring amino acids and nucleotides. It is important for sustainable aquaculture to replace animal protein with alternative protein sources such as black soldier fly larvae.